Out-of-hours primary percutaneous coronary intervention for ST-elevation myocardial infarction is not associated with excess mortality: a study of 3347 patients treated in an integrated cardiac network. Issue 6 (28th June 2013) - Rathod, Krishnaraj S; Jones, Daniel A; Gallagher, Sean M; Bromage, Daniel I; Whitbread, Mark; Archbold, Andrew R; Jain, Ajay K; Mathur, Anthony; Wragg, Andrew; Knight, Charles J
Abstract : Objectives: Timely delivery of primary percutaneous coronary intervention (PPCI) is the treatment of choice for ST-segment elevation myocardial infarction (STEMI). Optimum delivery of PPCI requires an integrated network of hospitals, following a multidisciplinary, consultant-led, protocol-driven approach. We investigated whether such a strategy was effective in providing equally effective in-hospital and long-term outcomes for STEMI patients treated by PPCI within normal working hours compared with those treated out-of-hours (OOHs). Design: Observational study. Setting: Large PPCI centre in London. Participants: 3347 STEMI patients were treated with PPCI between 2004 and 2012. The follow-up median was 3.3 years (IQR: 1.2–4.6 years). Primary and secondary outcome measures: The primary endpoint was long-term major adverse cardiac events (MACE) with all-cause mortality a secondary endpoint. Results: Of the 3347 STEMI patients, 1299 patients (38.8%) underwent PPCI during a weekday between 08:00 and 18:00 (routine-hours group) and 2048 (61.2%) underwent PPCI on a weekday between 18:00 and 08:00 or a weekend (OOHs group). There were no differences in baseline characteristics between the two groups with comparable door-to-balloon times (in-hours (IHs) 67.8 min vs OOHs 69.6 min, p=0.709), call-to-balloon times (IHs 116.63 vs OOHs 127.15 min, p=0.60) and procedural success. In hospital mortality rates were comparable between the two groups (IHs 3.6% vs OOHs 3.2%) with timing of presentation not predictive of outcome (HR 1.25 (95% CI 0.74 to 2.11). Over the follow-up period there were no significant differences in rates of mortality (IHs 7.4% vs OFHs 7.2%, p=0.442) or MACE (IHs 15.4% vs OFHs 14.1%, p=0.192) between the two groups. After adjustment for confounding variables using multivariate analysis, timing of presentation was not an independent predictor of mortality (HR 1.04 95% CI 0.78 to 1.39). Conclusions: This large registry study demonstrates that the delivery of PPCI with a multidisciplinary, consultant-led, protocol-driven approach provides safe and effective treatment for patients regardless of the time of presentation.